Library and Information Science Examination: A Report on Provisional Implementation in Japan / Hiroya Takeuchi, Akira Nemoto, Makiko Miwa... [et.al] al. - Takeuchi, Hiroya; Nemoto, Akira; Miwa, Makiko; Yoshida, Yuko; Aoyag, Eiji; Koyama, Kenji; Imai, Fukuji (2011)
This paper aims to describe the details of the challenging Library and Information Science (LIS) examinations, which the Japan Society of Library and Information Science (JSLIS) has conducted annually on a trial basis since 2007, and discuss some of observations. For such purposes, its objective, coverage of subject areas, examination style and reporting of results to students are described. We also discuss our experiences and observations of the provisional implementation of the LIS examination over the past four years. The results of the examination indicated that senior students achieved higher scores than junior students in general, and that the students from university LIS faculties achieved generally higher scores than did those from the Shisho certificate courses, which cover a more limited subject area of LIS than LIS specialty programs. These results suggest that the examination is a good measure of student proficiency, which reflects the quality of the educational programs. The problems to be solved before full-scale implementation can be summarized as follows: 1) the lack of standard textbooks covering the scope of the examination; 2) the low economic base for an annual examination; 3) lack of awareness of the need for this examination in standardizing the curricula for LIS education; and 4) the lack of a mechanism to implement the examination nationwide to facilitate participation by students living far from examination venues.